2018
DOI: 10.1002/chem.201804791
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self‐Sorting Networks using Hydrogen‐Bonding Motifs

Abstract: A current objective in supramolecular chemistry is to mimic the transitions between complex self‐sorted systems that represent a hallmark of regulatory function in nature. In this work, a self‐sorting network, comprising linear hydrogen motifs, was created. Selecting six hydrogen‐bonding motifs capable of both high‐fidelity and promiscuous molecular recognition gave rise to a complex self‐sorting system, which included motifs capable of both narcissistic and social self‐sorting. Examination of the interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…However, only CN has been substituted at all four positions because NH 2 forms intramolecular hydrogen bonds with the outer amine and carbonyl groups of the monomers, which has pronounced effects on the hydrogen bond strength. 6 Since we are purely interested in the remote substituent effects, we have therefore substituted NH 2 on positions 2 and 3 only. The names of the molecular systems include the type and position of the substituent in parentheses.…”
Section: Resultsmentioning
confidence: 99%
“…However, only CN has been substituted at all four positions because NH 2 forms intramolecular hydrogen bonds with the outer amine and carbonyl groups of the monomers, which has pronounced effects on the hydrogen bond strength. 6 Since we are purely interested in the remote substituent effects, we have therefore substituted NH 2 on positions 2 and 3 only. The names of the molecular systems include the type and position of the substituent in parentheses.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of HBMs from the toolkit of supramolecular synthons used to generate systems which can transition between different self‐sorted configurations arises because: (i) the requirements for high‐fidelity recognition may seem at odds with the need for promiscuous recognition required for transition between different self‐sorted states, (ii) HBMs that change recognition behavior in response to stimuli are sparse . Previously, our group demonstrated that a selection of HBMs could be used to create systems where successive addition of components changed the self‐sorted configuration (where at least one component exhibits promiscuous, and other components, selective recognition behavior), leading upon introduction of further components, to a self‐sorting network . The inability to switch recognition preference in a stimuli dependent manner remains a limitation of such a system.…”
Section: Figurementioning
confidence: 99%
“…More broadly these preliminary studies exemplify the power of an expanded supramolecular toolkit with which miscible blends can be prepared to order, with HBMs selected based on the strength of dimerization and knowledge of the immiscibility of the component polymers, to ensure maximum similarity and therefore properties to the respective un-functionalized polymers. Such studies together with the development of multi-component blends that exploit self-sorting 51,52 will represent the focus of our future studies.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%